2019
DOI: 10.47203/ijch.2019.v31i03.005
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and utilization of Geriatric Welfare Schemes among urban elderly population of District Gautam Budh Nagar

Abstract: Background: India has 8.6% elderly population which is going to increase to 12% by 2025. Government of India is providing for the elderly through various social security and welfare schemes as well as legislations. But various studies, mostly in rural areas have shown that the awareness regarding these schemes was poor and incomplete. Utilization of schemes by the beneficiaries was even poorer. Very few studies have assessed the same in urban areas. Aims & Objectives: To assess the awareness and utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The study concludes that teaching experience and training exposure were not significant capabilities to conduct eye health activities in the school. Agrawal et al, (2018) showed that a teacher's confidence in eye health education and promotional activities was low in different socio-demographic characteristics. This study shows the qualification-wise differences proved that most masters and the above-level teachers were more competent than other qualificationlevel teachers (Fry, Ketteridge, and Marshall, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The study concludes that teaching experience and training exposure were not significant capabilities to conduct eye health activities in the school. Agrawal et al, (2018) showed that a teacher's confidence in eye health education and promotional activities was low in different socio-demographic characteristics. This study shows the qualification-wise differences proved that most masters and the above-level teachers were more competent than other qualificationlevel teachers (Fry, Ketteridge, and Marshall, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the number of preschool teachers that completed the test the second time around was only 37% (60 teachers), the amount was still acceptable as the estimated number for test-retest to be carried out was 55, considering a significant level of 0.05, 80% of study power and expected ICC of 0.8 [34] . The psychometric properties of the KAP-VST questionnaire could not be compared to other studies because of the limited information in the development and validation process of these KAP studies [35][36][37] .…”
Section: A Questionnaire For Vision Screeningmentioning
confidence: 99%